Generation of high-energy neutrons with the 300-ps-laser system PALS. (1st June 2014) - KrÃ¡sa, J.; KlÃr, D.; Velyhan, A.; KrouskÃ½, E.; Pfeifer, M.; Å˜ezÃ¡Ä, K.; Cikhardt, J.; Turek, K.; Ullschmied, J.; Jungwirth, K.
Abstract The laser system PALS, as a driver of a broad-beam ion source, delivered deuterons which generated neutrons with energies higher than 14Â MeV through the <alternatives><inline-graphic xlink:href="ark:/27927/pgj449hc29" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> <![CDATA[$\def \xmlpi #1{}\def \mathsfbi #1{\boldsymbol {\mathsf {#1}}}\let \le =\leqslant \let \leq =\leqslant \let \ge =\geqslant \let \geq =\geqslant \def \Pr {\mathit {Pr}}\def \Fr {\mathit {Fr}}\def \Rey {\mathit {Re}}{}^{7}\mathrm{Li(d, n)}{}^{8}\mathrm{Be}$]]> </alternatives> reaction. Deuterons with sub-MeV energy were accelerated from the front surface of a massive <alternatives><inline-graphic xlink:href="ark:/27927/pgj449hm8s" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> <![CDATA[$\mathrm{CD}_{2}$]]> </alternatives> target in the backward direction with respect to the laser beam vector. Simultaneously, neutrons were emitted from the primary <alternatives><inline-graphic xlink:href="ark:/27927/pgj449gz9p" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> <![CDATA[$\mathrm{CD}_{2}$]]> </alternatives> target and a secondary LiF catcher. The total maximum measured neutron yield from <alternatives><inline-graphic xlink:href="ark:/27927/pgj449hb6w" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> <![CDATA[${}^{2}\mathrm{D(d, n)}{}^{3}\mathrm{He}$]]> </alternatives>, <alternatives><inline-graphic xlink:href="ark:/27927/pgj449jb49" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> <![CDATA[${}^{7}\mathrm{Li(d, n)}{}^{8}\mathrm{Be}$]]> </alternatives>, <alternatives><inline-graphic xlink:href="ark:/27927/pgj449f6hq" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> <![CDATA[${}^{12}\mathrm{C(d, n)}{}^{13}\mathrm{N}$]]> </alternatives> reactions was <alternatives><inline-graphic xlink:href="ark:/27927/pgj449hvcq" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> <![CDATA[${\sim } 3.5 ({\pm }0.5) \times 10^{8}\ \mathrm{neutrons/shot}$]]> </alternatives>.